Evaluation of integrated pest management modules for insect pests in short duration pigeonpea (Canjas cajan) in eastern Uttar Pradesh - JOSHI, NITIN; SRIVASTAVA, C P (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during rainy season (Kharf) 2001 and 2002 to evaluate the effectiveness of 5 IPM modules for the pests of pigeonpea (Cajanus cajan (L.) Millsp.) Amongst the various modulese valuated against the pests of ’UPAS 120’ pigeonpea; module 2 (M2) could effectively manage the population of Helicoverpa armigera (Hubner) and Melanagromryza obtuse Malloch. Grain yield was also significantly higher (767.8 and 796.7 kgl/ha in 2001 and 2002 respectively) in comparison to other modules including farmer’s practice. The highest C : B ratio’s of 1 :3.22 and I :3.35 were recorded in this module during both the years.